A Corpus-based Cognitive Analysis of the Radial Category GREEN in Arabic - Lahlou, Hicham (Pusat Pengajian Ilmu Kemanusiaan, 2019)
From a Cognitive linguistic perspective, language is a communication system that mirrors human beings’ understanding of the world around them (Cienki, 2007). Words are not containers of meaning, but rather they provide access to a cognitive network (Langacker, 1987). The senses that words have are not fixed or restricted, but they evoke a variety of cognitive domains based on context (Langacker, 1999). The senses of a word are not discrete. Rather, they fall into a continuum along which they overlap and share some common properties. The meanings that exhibit more common features are typical while those that show less common attributes are peripheral. Within this approach, a semantic change takes place when a peripheral sense becomes the core meaning of a lexical unit, or a typical meaning is excluded from the prototype structure of the word (Carpenter, 2013).